EVALUASI IMPLEMENTASI SUPERVISI MANAJERIAL DALAM MENINGKATKAN KINERJA ADMINISTRATIF DI INSTITUSI PENDIDIKAN - Simatupang, Anggi Nauli; Waruwu, Marinu; Halida, Halida; Enawaty, Eny (Universitas Tanjungpura, 2025)
This research evaluates the implementation of managerial supervision to enhance administrative performance in educational institutions. The study aims to analyze how managerial supervision influences administrative efficiency and effectiveness, particularly in schools located in remote or underdeveloped areas. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings reveal that effective managerial supervision positively impacts administrative performance by fostering a culture of collaboration, professional growth, and data-driven decision-making. However, several challenges were identified, including limited resources, inadequate training for supervisors, and inconsistent participation from staff. The study highlights the importance of involving all stakeholders in the supervision process to ensure continuous improvement and long-term success in administrative tasks. It also suggests that regular evaluations of supervision practices are essential for identifying areas needing improvement and for refining supervisory methods. Overall, this research underscores the critical role of managerial supervision in driving institutional efficiency and improving the quality of educational administration